Optimisation and validation of immunohistochemical axonal markers for morphological and functional characterisation of equine peripheral nerves. (19th January 2021) - Almuhanna, Abdulaziz H.; Cahalan, Stephen D.; Lane, Annette; Goodwin, David; Perkins, Justin; Piercy, Richard J.
Abstract: Background: Horses are affected by various peripheral nerve disorders but defining their aetiology and pathophysiology is hampered by limited understanding of associated morphological and pathological changes and involvement of specific axonal types. Objectives: To investigate the hypothesis that selected antibody markers, used in conjunction with various tissue processing methods, would enable identification of axons with different functional modalities within a range of equine peripheral nerves. Study design: Optimisation and validation study. Methods: A range of antibodies were evaluated immunohistochemically via fluorescence confocal microscopy in cadaver equine nerve samples of primary motor, mixed or primary sensory functions (recurrent laryngeal, phrenic and plantar digital) within formalin‐fixed paraffin‐embedded (FFPE) and formalin‐fixed frozen (FFF) tissues subjected to different antigen retrieval protocols. Results: Immunohistochemistry of FFPE‐derived nerve samples with selected antibodies and specific antigen retrieval methods enabled identification of myelinated and unmyelinated axons, cholinergic, sympathetic and peptidergic axons. The recurrent laryngeal and phrenic nerves are composed of myelinated cholinergic (motor), myelinated sensory fibres, unmyelinated adrenergic (sympathetic) axons and unmyelinated peptidergic (sensory) axons. In contrast, as expected, the plantar digital nerve had no myelinated motor fibres being mainly composed of myelinated sensory fibres, unmyelinated sympathetic and unmyelinated peptidergic sensory axons. Main limitation: Attempts specifically to label parasympathetic fibres were unsuccessful in any nerve examined in both FFPE and FFF tissues. Conclusions: A panel of antibody markers can be used to reveal morphological and functional properties of equine nerves. Future work should enable better characterisation of morphological changes in equine neuropathies at various stages of disease development.